Development of IoT-Based Dual-Channel Battery Charger with Real-Time Monitoring - Agoeng Harjatmo Rahardjo; Erwin Yusuf; Wildan Arasid (Universitas Sebelas Maret (UNS), 2026)
The development of efficient and controlled battery charging systems has become increasingly important with the growing use of electronic devices and energy storage systems. This research aims to develop an Internet of Things (IoT)-based charger monitoring and control system for optimizing the 12 V battery charging process. The developed system employs a dual-channel architecture capable of serving two batteries with automatic and manual operation capabilities. The main system components include a voltage divider-based voltage sensor, ACS712-5A current sensor, ESP32 microcontroller, dual-channel relay, and a Nextion 2.7-inch LCD touchscreen as the user interface. The IoT platform utilizes the Blynk application, enabling remote monitoring and control via smartphone. Test results demonstrate that the system is capable of monitoring charging parameters with high accuracy and providing responsive control both locally and remotely. The system successfully implements adaptive automatic charging logic based on battery conditions and provides safety features to prevent overcharging. This research contributes to the development of smart charger technology that can improve charging efficiency and extend battery lifespan.